Continuing the journey to reposition culture and cultural context in evaluation theory and practice - Hood, Stafford; Hopson, Rodney K.; Frierson, Henry T. (Evaluation and society., 2015)
Racial, ethnic, linguistic, and cultural diversity has become of global importance in places where many never would have imagined. Increasing diversity in the U.S., Europe, Africa, New Zealand, and Asia strongly suggests that a homogeneity- based focus is rapidly becoming an historical artifact. This book highlights that culturally responsive evaluation (CRE) should no longer be viewed as a luxury or an option in our work as evaluators and this perspective requires a distinct shift from "simple" linear cause-effect models and reductionist thinking to include more holistic and culturally responsive approaches.This book expands on Culturally Responsive Evaluation, exploring theory and practice globally. It highlights indigenous perspectives from North America and New Zealand while examining immigrant and Roma experiences in Europe, emphasizing its growing international relevance.